Challenges in Applying a Student-Centred Approach to E-Learning for Islamic Education in Primary Schools during the Pandemic Covid-19: Preliminary Data Analysis - Tengku Kasim, Tengku Sarina Aini; Mohd Noor, Nur Eliza; Md Yusoff, Yusmini (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
COVID-19 pandemic has changed the world significantly in various sectors and industries, including the educational sector. For example, traditional classroom learning, which is more teacher-centred, is being replaced by e-learning, which takes a student-centred approach. However, this approach is considered distinct from the teaching and learning practice of Islamic Education taught in the classroom before the pandemic. This sudden shift presents a significant challenge to Islamic Education teachers to apply more student-centred e-learning. According to the literature review, several issues arose when Islamic Education e-learning was implemented, such as low student engagement, few active students, little student feedback, and high student dropout rates. Thus, this preliminary study examined the challenges of implementing the student-centred approach to e-learning for Islamic Education in primary schools. This study adopted a qualitative design with an in-depth interview involving Islamic Education teachers in primary schools. The study’s findings revealed that the research informants continuously implemented the student-centred approach even when the country was struck by the COVID-19 pandemic, despite facing challenges, especially in student personality development. Moreover, the findings suggest that teachers must better comprehend and implement a more creative student-centred approach in e-learning to align with 21st-century education and fulfil their responsibility for students’ future personality development.